The Effect of Price Perception and Shopping Lifestyle on Impulse Buying at TikTok Shop among Generation Z in Surabaya City - Hermawan, Tomy; Dermawan, Rizky (PT FORMOSA CENDEKIA GLOBAL, 2023)
During this era of rapid technological advancement, human needs for access to information and the ability to interact with others have become easier to achieve through one of the main means, namely the use of social media platforms. The aim of this study was to determine the impact of price perceptions and shopping lifestyles on impulse buying at TikTok Shop among generation Z in Surabaya city. This study applies a quantitative approach by collecting primary data obtained from questionnaires. The sampling method used is non-probability sampling and purposive sampling, where 104 individual respondents who live in Surabaya and use TikTok Shop are the subjects in this study. Data analysis was analyzed using SmartPLS 4.0. This study reveals that price perception and shopping lifestyle have a positive and significant influence on impulse buying at TikTok Shop, especially for generation Z in Surabaya.